Penentuan Harga Pokok Produksi Dengan Metode Full Costing Sebagai Dasar Penetapan Harga Jual Pada UKM Tahu AN Anugrah - Anggreani, Sintia; Adnyana, I Gde Sudi (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
Cost of Goods Manufacture is an important component that must be calculated by the company in order to determine the selling price of the product. SMEs are often wrong in calculating the Cost of Goods Manufacture they do. One of the mistakes made by SMEs in calculating the Cost of Goods Manufacture is that the calculations carried out are very simple and do not specify all costs used in the production process to produce a product. This study aims to analyze (1) the calculation of the Cost of Goods Manufacture in SMEs Tahu AN Anugrah , (2) the determination of Cost of Goods Manufacture with the full costing method in SMEs Tahu AN Anugrah, and (3) the difference in calculation of Cost of Goods Manufacture according to SMEs AN Anugrah and according full costing method and its effect on selling prices. The data used in this study are primary data and secondary data. The primary data used is obtained from the results of interviews and recording of information needed directly in SMEs Tahu AN Anugrah. While the secondary data are is obtained from literature studies such as previous journals, related books, documentation and reading in accordance with the research title. The Research results show, there are differences in the calculation results of the Cost of Goods Manufacture carried out by the SMEs and by the full costing method. The calculation of Cost of Goods Manufacture by SMEs Tahu AN Anugrah for White Tofu products is Rp 200 and Yellow Tofu Rp 201.12 while by the full costing method for White Tofu products is Rp 218.41 and Yellow Tofu Rp 228.44. So that, there are differences in the calculation results, namely for White Tofu Rp 18.41 and Yellow Tofu Rp 27.32. Differences in calculation are due to the full costing method is more detailed by including all elements of production costs. This shows that the method provides a more accurate calculation to be able to set a better selling price. Keywords: Cost of Goods Manufacture, Full Costing, Selling Prices, SMEs